RESILIENSI KOMUNIKASI BISNIS UMKM SYARIAH TERHADAP REGULASI DIGITAL: DAMPAK MISKOMUNIKASI KEBIJAKAN DISKON KURIR E-COMMERCE - Pirman Padilah; Muhamad Ilham Mauludin (Gunung Djati Conference Series, 2025)
Sharia Micro, Small, and Medium Enterprises (MSMEs) increasingly navigate complex digital regulations, where miscommunication, particularly concerning e-commerce courier discount policies, poses significant operational challenges. This study explores the communication resilience strategies employed by Sharia MSMEs in responding to such digital policy miscommunication. Adopting a qualitative case study approach, this research, conducted in May 2025 in Bandung, West Java, involved in-depth interviews with a Sharia-compliant MSME, UMKM Mohaki, to understand its experiences and adaptive communication practices. Findings indicate that the MSME demonstrates resilience through proactive external communication with stakeholders and adaptive digital information-seeking behaviors, despite facing partial understanding of regulations due to reliance on informal channels. The informal integration of Islamic values like honesty and trustworthiness further underpins their business ethics and stakeholder engagement. Conclusively, the communication resilience of Sharia MSMEs is a dynamic interplay of active stakeholder dialogue, embedded ethical principles, and digital adaptability, though significantly challenged by unclear direct communication from regulators. This research contributes to understanding the nuanced communication strategies that enable Sharia MSMEs to maintain operational stability amidst the uncertainties of the digital regulatory landscape.